Characterization of Steam Reforming Catalyst in Solid Oxide Fuel Cell Using Biogas - Chung, Jindo; Han, Yujin (Asian Journal of Chemistry, 2013)
This study described to produce hydrogen gas from recyclable biomass steadily and stably and use this resulting hydrogen effectively as an energy source of solid oxide fuel cell. We chose the steam reforming reaction as a model reaction and compared several catalytic activities with several different common and uncommon catalysts. We analyzed the amount of carbon adsorption by using scanning electron microscope and performed thermogravimetric analysis for reaction variables of several catalysts. We also used the reformed gas produced by different catalysts as energy source for solid oxide fuel cell (SOFC) and characterized the electrical properties of SOFC for the different catalysts. The comparison of three catalysts (Ru, Ni and Ni/Ru) shows that the reaction activity is higher in the order of Ru(0.5 wt%)/Ni(20 wt%)/Al2O3 > Ni(20 wt%)/ Al2O3 > Ru(2 wt%)/Al2O3. The resistance of catalyst against coking under the S/C ratio of 2.5 was turned out to be better in the order of Ru(2 wt%)/Al2O3 > Ru(0.5 wt%)/Ni(20 wt%)/Al2O3 > Ni(20 wt%)/Al2O3. The electrical analysis of solid oxide fuel cell for the different catalysts at 750 ºC and under the S/C ratio of 2.5 shows that the initial voltage was identical for all catalysts, however, it starts to show the difference after a long operation (160 h) that the electrical property is superior in the order of Ru(0.5 wt%)/Ni(20 wt%)/Al2O3 > Ni(20 wt%)/Al2O3 > Ru(2 wt%)/ Al2O3.